The Predictive Value of Fair Value Adjustment in Other Comprehensive Income (OCI): Evidence from ASEAN Banking Industry - Latif, Dwianto Mukhtar; ., Isnalita (Journal of Posthumanism, 2025)
This study aims to examine the predictive value of the fair value adjustment contained in other comprehensive income (OCI). In particular, the test was conducted to see the ability of OCI to predict the next 1 and 2 years the company’s performance as measured using pre-tax ROA. Using a sample of banking industries registered in ASEAN countries, this study tested the OLS regression with a sample size of 805 firm-years for predictions of 1 year ahead, and 690 firm-years for predictions of 2 years into the future. The results showed that the fair value adjustment contained in the OCI proved to have predictive value for the next 1 and 2 years. Furthermore, tests based on the classification of fair value levels, show that fair value levels 1 and 2 have more predictive value than fair value level 3. Overall, these results support the IASB and IASB claims that fair value accounting meets financial reporting objectives by providing information that is useful in decision making.